Understanding the Criminogenic Properties of Vacant Housing: A Mixed Methods Approach. (May 2019) - Porter, Lauren C.; De Biasi, Alaina; Mitchell, Susanne; Curtis, Andrew; Jefferis, Eric
Objectives: Abandoned houses may attract or generate crime; however, little is known about the nature of this relationship. Our study is aimed at better understanding this link. Methods: Focusing on a high-crime neighborhood in Ohio, we use spatial video and calls for service (CFS) to examine how crime changed on streets where abandoned homes were removed. We also draw on the insights of 35 ex-offenders, police officers, and residents to examine how and why abandoned houses are connected to crime in this locale. Results: On average, streets where abandoned houses were razed accounted for a lower proportion of neighborhood crime after removal. Also, a lower proportion of total CFS from these streets related to serious crime. Our narrative data indicate that abandoned houses are opportunistic because they provide cover, unoccupied spaces, and are easy targets. Conclusions: The removal of abandoned housing was associated with positive changes in crime overall; however, our approach revealed interesting variation across streets. We surmise that the relevance of a particular abandoned house may be contingent on the larger context of that street or neighborhood. In order to understand these dynamics, future research should continue to "drill down" into micro-spaces.